A new species of extinct genus Electromyiomma Popov & Herczek (Hemiptera: Miridae: Isometopinae) from Eocene Baltic amber, with the key to Electromyiomma species - Kim, Junggon; Jung, Sunghoon (Zootaxa, 2021)
A new fossil isometopine species, Electromyiomma herczeki sp. nov. is described and illustrated from Eocene Baltic amber. The morphological information of the fossil specimen and the key to the species of the extinct genus Electromyiomma are provided. The restatement of paratype female of E. weitschati is discussed with the support of previous remarks based on antenna structure.